Whole-body bioluminescence imaging of T-cell response in PDAC models - McMorrow, Roisin; Zambito, Giorgia; Nigg, Alex; Lila, Karishma; van den Bosch, Thierry P. P.; Lowik, Clemens W. G. M.; Mezzanotte, Laura (Frontiers in Immunology, 2023)
Introduction The location of T-cells during tumor progression and treatment provides crucial information in predicting the response in vivo. Methods Here, we investigated, using our bioluminescent, dual color, T-cell reporter mouse, termed TbiLuc, T-cell location and function during murine PDAC tumor growth and checkpoint blockade treatment with anti-PD-1 and anti-CTLA-4. Using this model, we could visualize T-cell location and function in the tumor and the surrounding tumor microenvironment longitudinally. We used murine PDAC clones that formed in vivo tumors with either high T-cell infiltration (immunologically ‘hot’) or low T-cell infiltration (immunologically ‘cold’). Results Differences in total T-cell bioluminescence could be seen between the ‘hot’ and ‘cold’ tumors in the TbiLuc mice. During checkpoint blockade treatment we could see in the tumor-draining lymph nodes an increase in bioluminescence on day 7 after treatment. Conclusions In the current work, we showed that the TbiLuc mice can be used to monitor T-cell location and function during tumor growth and treatment.